Physico-Chemical Evaluation for Allium hookeri Thw. Enum Leaves - Nepram Swarnalata; Shailendra Sharma (International Journal of Phytomedicine, 2016)
Awareness and general acceptability of the natural products is increasing day by day because of its lesser side effect and cost factor. Above 80% of the world population is depending upon herbal medicines. Use of plants as medicine is the oldest practice that has been used in all countries from ancient time. Based on those old practices medicines of modern days are derived either directly or indirectly from the natural products. Manipur is one of the north eastern states of India and one of the hot spot areas of biodiversity, blessed with the amazing variety of flora and fauna. Allium hookeri belongs to Alliaceae family and is a perennial herb growing in dampy soil in every kitchen garden in Manipur. It is locally known as Maroi Napakpi and used as spice and condiment in almost all Manipuri dishes. Its taste is preferred over onion in Manipur.Fresh leaves and fibrous roots are used as medicine in reducing temperature, in swelling as an antimicrobial and antioxidant and reducing blood cholesterol etc. It is reported that its root has antioxidant, free radical scavenging, antimicrobial and anti-inflammatory action. In Manipur people are taking fresh green leaves for many ailments like reducing temperature, reducing blood cholesterol, etc.. So the present study has been carried out to evaluate pharmacognostic and physicochemical analysis of shade dried leaves of Allium hookeri.. The reported information will provide data which will be useful in proper identification and authentification of this plant for future research work.